DIVERSITY AND CAPABILITY ANALYSES OF FERTILITY RESTORER GENES OF CYTOPLASMIC MALE STERILE RICE LINES USING SSR - Yuni Widyastuti; Muhamad Yunus; Bambang Sapta Purwoko; Satoto Satoto (Indonesian Journal of Agricultural Science, 2017)
Development of hybrid rice depends on the effectivity of cytoplasmic male sterility (CMS) and restorer (R) lines.  The molecular genetic approach is expected to help the breeder in identification of suitable parental lines to hybrid rice improvement. The study aimed to assess genetic relationship among three types of CMS systems (wild  abbortive/WA Kalinga and Gambiaca) as female parents and to identify diversity of genes controlling fertility restoration in rice. The study used nine F1 hybrids and F2 populations obtained from the hybridization of three different CMS lines (IR58025A-WA, IR80156A-Kalinga and IR80154A-Gambiaca) with three restorer lines (PK90, PK12 and BP11). Fifteen SSR markers were used to select genomic regions of chromosome 1 and 10 on which Rf3 and Rf4 genes located in the hybrids. The results showed that fertility restoration in CMS-WA and CMS-Gambiaca was governed by two independent and dominant genes (Rf3 and Rf4), while in CMS-Kalinga the fertility restoration was controlled by one single dominant gene. Biological processes occurred in the fertility restoration of the hybrids were the same based on the pollen and spikelet fertilities of F1 hybrids derived from three CMS and R lines, i.e. 76.1–78.3% and 69.1–76.6%, respectively. A restorer line PK12 had a higher capability in fertility restoration than PK90 and BP11. The SSR primers RM490 and RM258 were capable of identifying the Rf3 and Rf4 genes controlled fertility restoration in CMS-WA. The study supports the use of male sterile WA in rice hybridization.